2008
DOI: 10.1007/s00213-008-1160-5
|View full text |Cite
|
Sign up to set email alerts
|

Cataleptic effects of γ-hydroxybutyrate (GHB) and baclofen in mice: mediation by GABAB receptors, but differential enhancement by N-methyl-d-aspartate (NMDA) receptor antagonists

Abstract: Rationale-Gamma-hydroxybutyrate (GHB) is a gamma-aminobutyric acid (GABA) analog that is used to treat narcolepsy but that is also abused. GHB has many actions in common with the GABA B receptor agonist baclofen, but their underlying GABA B receptor mechanisms may be different.Objective-The aim of this study is to further investigate a possible differential role of glutamate in GABA B receptor-mediated effects of GHB and baclofen. Materials and methods-The experiments examined the effects of non-competitive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
6
22
0
1
Order By: Relevance
“…However, there is growing evidence that the GABA B receptor mechanisms underlying the effects of baclofen and GHB are not identical. First, differential enhancement of behavioral effects (discriminative stimulus effects, catalepsy) of baclofen and GHB by N-methyl-D-aspartate antagonists suggests that the GABA B receptors involved in these effects of baclofen and GHB are not identical (Koek et al, 2007a;Koek and France, 2008). Second, differential antagonism of behavioral effects of baclofen and GHB by CGP35348, reported previously (Koek et al, , 2007bCarter et al, 2006) and also observed in the present study, is further evidence that different GABA B receptor populations mediate these effects of baclofen and GHB.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, there is growing evidence that the GABA B receptor mechanisms underlying the effects of baclofen and GHB are not identical. First, differential enhancement of behavioral effects (discriminative stimulus effects, catalepsy) of baclofen and GHB by N-methyl-D-aspartate antagonists suggests that the GABA B receptors involved in these effects of baclofen and GHB are not identical (Koek et al, 2007a;Koek and France, 2008). Second, differential antagonism of behavioral effects of baclofen and GHB by CGP35348, reported previously (Koek et al, , 2007bCarter et al, 2006) and also observed in the present study, is further evidence that different GABA B receptor populations mediate these effects of baclofen and GHB.…”
Section: Discussionsupporting
confidence: 85%
“…First, the GABA B receptor antagonist 3-aminopropyl(diethoxymethyl) phosphinic acid (CGP35348) antagonizes the behavioral effects of GHB (discriminative stimulus effects, suppression of operant responding, catalepsy) less potently than those of baclofen (Koek et al, , 2007bCarter et al, 2006). Second, N-methyl-D-aspartate antagonists enhance the behavioral effects of GHB (discriminative stimulus effects, catalepsy), but not those of baclofen (Koek et al, 2007a;Koek and France, 2008). Preferential activity of GHB at GABA B heteroreceptors on glutamatergic neurons and baclofen at GABA B autoreceptors on GABAergic neurons could conceivably account for some of these differences (Carter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The cataleptic effects of GHB are enhanced not only by MK-801 but also by other drugs with NMDA antagonist activity, such as phencyclidine (PCP) and ketamine. However, these NMDA antagonists do not affect the cataleptic effects of baclofen (Koek and France, 2008). Similar interactions have been observed in drug discrimination studies; PCP enhances the discriminative stimulus effects of GHB but not of baclofen (Koek et al, 2007a).…”
supporting
confidence: 74%
“…The NMDA antagonist PCP and GHB enhance each other's discriminative stimulus effects, but PCP and baclofen do not, suggesting that the mechanisms underlying these effects of GHB and baclofen are differentially modulated by the glutamatergic system with which PCP interacts (Koek et al, 2007a). The recent finding that PCP and other antagonists at the NMDA subtype of glutamate receptors enhance the cataleptic effects of GHB but not those of baclofen (Koek and France, 2008) provides further evidence that the GABA B receptor systems mediating the effects of GHB and baclofen are differentially modulated by glutamate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation